Barriers for the implementation of Kangaroo mother care practice - Matassini-Eyzaguirre, Silvana M. (2021)
Objetives: Analyse and discuss the barriers to the implementation of the Kangaroo Mother Method (KMC) in a social security hospital in Lima, Peru. Material and Methods: Qualitative study with ethnographic design carried out between October 2019 and January 2020. Observation and in-depth interviews were the information collection tools used, conducted with mothers, family members, and health personnel (HCP). Results: The most outstanding barriers to the application of the KMC were those related to the humane treatment and knowledge about the KMC by health personnel. On the part of kangaroo mothers, it is the economic and family aspects that negatively influence their involvement in the MMC. Conclusions: Despite the limitation of hospital resources, the mothers stated that carrying out the KMC is challenging mainly due to the weak relationship with some members of the health personnel. It is important to invest, as a priority, in the human capital involved to contribute to the sustainable transfer and effective care of the premature baby at a household level.